The Impact of Regulation Readiness and Collaboration in Empowering Business Model Innovation in IoT Companies - Muhamad Yopan (Green Publisher Indonesia, 2025)
This study investigates the influence of perceive regulation readiness and collaboration on business model innovation and business performance in the Internet of Things (IoT) Companies. With IoT’s rapid growth, companies face the challenge of continually adapting their business models to evolving customer needs and regulatory frameworks. Drawing on contingency theory, the study emphasizes that no single strategy fits all organizations and that constant innovation is essential for sustainable success. Data was collected from 75 IoT companies in Indonesia, analyzed using SmartPLS to assess relationships among the variables. Findings reveal that regulatory readiness positively influences collaboration, which in turn significantly enhances business model innovation. Business model innovation is shown to directly impact business performance, highlighting its critical role in achieving competitive advantage. However, the study finds no significant moderating effects of regulatory readiness or collaboration on the relationship between business model innovation and performance, suggesting that these factors act independently rather than as moderators. Additionally, the study underscores the importance of IoT security standards, particularly in balancing technical and non-technical considerations such as data privacy. The findings provide insights into the strategic importance of adaptable business models and the need for regulatory frameworks to support IoT innovation effectively.